(untitled) (American Journal of Pedagogical and Educational Research, 2026)
The article provides a well-founded scientific explanation of rock music, human health, and its impact on child development. The article highlights interesting facts about how music teaches not only to listen, but also to hear, not only to look, but also to see, hear, and feel. Also, the sequential flashes of light in accordance with the rhythm of the music are based on the mechanisms associated with hallucinations, dizziness, and nausea. In addition, it is highlighted that musical training can develop mental development and thinking skills, develop memory, calm rhythmic music can calm a newborn baby, but prolonged listening creates a constant excitation process in the brain.